Fish Community Structure in Seagrass Ecosystem at Tiwoho Village Coast, North Sulawesi (Struktur Komunitas Ikan Di Ekosistem Padang Lamun Pantai Desa Tiwoho, Sulawesi Utara) - Panjaitan, Cristiani Br; Rondonuwu, Ari B.; Rembet, Unstain N.W.J.; Mandagi, Stephanus V.; Kondoy, Kristin I. F.; Mantiri, Rose O. S. E. (Journal of Aquatic Resources Bioecology, 2026)
Seagrass ecosystems play an important role as habitats for various coastal fish species, but information on the structure of fish communities in North Minahasa is still limited. This study aims to analyze the structure of fish communities in the seagrass meadows of Tiwoho Village Beach, which is part of the Bunaken National Park conservation area. Fish sampling used beach seines with three replications at three sampling points in December 2025. The results showed that the fish community consisted of 24 species from 21 families with a total of 156 individuals. Osteomugil cunnesius had the highest relative abundance (25.00%). The Shannon-Wiener diversity index (H' = 2.55) indicated moderate diversity, the evenness index (J' = 0.80) was classified as almost even, and the dominance index (C = 0.12) was classified as low, reflecting a relatively balanced community structure. Water quality parameters (temperature: 29.56–34.45°C; pH: 8.10–8.58; dissolved oxygen: 6.52–7.09 mg/L; salinity: 31.26–31.49 ppt) are within the optimal range for marine fish. Seagrass beds in Tiwoho Village support a stable fish community with ecological functions as a nursery, feeding ground, and habitat for coastal fish species Abstrak. Ekosistem lamun memainkan peran penting sebagai habitat bagi berbagai spesies ikan pesisir, namun informasi mengenai struktur komunitas ikan di Minahasa Utara masih terbatas. Penelitian ini bertujuan untuk menganalisis struktur komunitas ikan di padang lamun Pantai Desa Tiwoho, yang merupakan bagian dari kawasan konservasi Taman Nasional Bunaken. Pengambilan sampel ikan menggunakan pukat pantai dengan tiga ulangan di tiga titik pengambilan sampel pada bulan Desember 2025. Hasil penelitian menunjukkan bahwa komunitas ikan terdiri dari 24 spesies dari 21 famili dengan total 156 individu. Osteomugil cunnesius memiliki kelimpahan relatif tertinggi (25,00%). Indeks keanekaragaman Shannon-Wiener (H' = 2,55) menunjukkan keanekaragaman sedang, indeks keseragaman (J' = 0,80) diklasifikasikan sebagai hampir merata, dan indeks dominasi (C = 0,12) diklasifikasikan sebagai rendah, yang mencerminkan struktur komunitas yang relatif seimbang. Parameter kualitas air (suhu: 29,56–34,45°C; pH: 8,10–8,58; oksigen terlarut: 6,52–7,09 mg/L; salinitas: 31,26–31,49 ppt) berada dalam kisaran optimal untuk ikan laut. Padang lamun di Desa Tiwoho mendukung komunitas ikan yang stabil dengan fungsi ekologis sebagai tempat pembibitan, tempat makan, dan habitat bagi spesies ikan pesisir